Delphinids of southern Africa: A review of their distribution, status and life history - Peddemors, V.M. (J. Cetacean Res. Manage., 2023)
Eighteen species of delphinids have been recorded from Africa, south of l 7°S. This review includes analyses of the distribution and status, life history and feeding habits for each species, primarily using published data from strandings, incidentally caught animals and sightings. Although there is little known for most of the species distributed over the continental shelf, it appears that there is presently little human-induced threat to these. However, more research emphasis should in future be placed on possible detrimental interactions due to overfishing of delphinid prey stocks. Increased commercial fishing pressure will inevitably also increase interactions between the fishery and the affected delphinids. Only three inshore species are presently considered to be vulnerable: Heaviside’s dolphins (Cephalorhynchus heavisidil), bottlenose dolphins (Tursiops truncatus) in KwaZulu-Natal and Namibia, and Inda-Pacific hump-backed dolphins (Sousa chinensis) in KwaZulu-Natal. Heaviside’s dolphins are endemic and, although presently probably able to sustain mortalities following interactions with commercial fishing gear, may become negatively impacted should fishing activities increase. The bottlenose dolphin population in Namibia appears localised in its distribution and may therefore also be vulnerable to any future coastal development or commercial fishery expansions, while in KwaZulu-Natal they are subjected to ongoing incidental catches in shark nets, heavy pollution levels, habitat destruction and increased competition with fishermen for limited food resources. In KwaZulu-Natal, Inda-Pacific hump-backed dolphins are subjected to the same pressures as experienced by bottlenose dolphins, albeit more severely, while in Mozambique it is occasionally caught incidentally in gillnets or in a targeted fishery. Although generally considered an offshore species, southern right whale dolphins (Lissodelphis peronii) also appears to be extremely localised in distribution within southern Africa, and any future planned expansion of commercial driftnet fisheries off Namibia should be carefully monitored for incidental catches which may impact this population.